Regionalization Analysis of Ruminant Livestock Commodities in Majalengka Regency Using the Location Quotient Method - Itang Purnama; Dini Widianingrum; Irma; Abdul Muta Ali; Fikya Juanda; Raden Febrianto Christi (Fakultas Pertanian Universitas Majalengka, 2025)
The ruminant livestock sector constitutes a critical component in ensuring food security and strengthening regional economies, thereby necessitating spatial analyses to identify its development potential. This study employed secondary data from the Central Bureau of Statistics (BPS) of Majalengka Regency covering the period 2020–2024. The objective was to examine the spatial distribution and regionalization of ruminant livestock enterprises using the Location Quotient (LQ), Localization Index (LI), and Specialization Index (SI). The commodities analyzed comprised sheep, goats, cattle, and buffalo across sub-districts within the regency. The findings revealed that sheep represent the dominant commodity, characterized by consistently high LQ, LI, and SI values, thus establishing their role as the primary basis for regional livestock development. Goats demonstrated moderate index values, indicating potential as an alternative for expansion. Cattle exhibited relatively even distribution across sub-districts but were not identified as a leading commodity. Buffalo recorded the lowest index values, underscoring their role as a complementary species. These results underscore the importance of commodity-based planning, particularly emphasizing sheep development, to enhance the competitiveness and sustainability of the livestock sector in Majalengka Regency.